Fc alpha receptors mediate release of tumour necrosis factor-alpha and interleukin-6 by human monocytes following receptor aggregation. - Patry, C (1995)
The functional capacity of the human monocyte receptor for the Fc portion of IgA (Fc alpha R) in mediating signal transduction was evaluated by cytokine release. F(ab')2 fragments of anti-Fc alpha R monoclonal antibodies (mAb) were used as specific probes to induce release of tumour necrosis factor-alpha (TNF-alpha) and interleukin-6 (IL-6). Multivalent cross-linking by a secondary anti-mouse antibody [F(ab')2 fragments] induced a significant release of TNF-alpha and IL-6 by human blood mononuclear cells, indicating requirements for Fc alpha R aggregation on the cell surface to transmit signals. Both cytokines were released exclusively by adherent cells, identifying monocytes as the responding cells within the mononuclear cell population. This cytokine release could not be due to contaminating endotoxins, because it was not abolished by polymyxin B, a lipopolysaccharide (LPS) inhibitor. Moreover, purified recombinant soluble Fc alpha R inhibited the anti-Fc alpha R mAb-mediated cytokine release from blood monocytes, demonstrating that TNF-alpha and IL-6 were released in a receptor-specific manner. Our data suggest that Fc alpha R, through its capacity to mediate secretion of IL-6, may play an important role in B-cell proliferation and immunoglobulin production. On the other hand, release of TNF-alpha following stimulation of Fc alpha R molecules directly implicates these receptors in amplification and regulation of the inflammatory process occurring during IgA-mediated host defence.